Low levels of exosomal-miRNAs in maternal blood are associated with early pregnancy loss in cloned cattle. Issue 1 (December 2017) - Bem, T.; Silveira, J.; Sampaio, R.; Sangalli, J.; Oliveira, M.; Ferreira, R.; Silva, L.; Perecin, F.; King, W.; Meirelles, F.; Ramos, E.
Abstract Nuclear reprogramming mediated by somatic cell nuclear transfer (SCNT) has many applications in medicine. However, animal clones show increased rates of abortion and reduced neonatal viability. Herein, we used exosomal-miRNA profiles as a non-invasive biomarker to identify pathological pregnancies. MiRNAs play important roles in cellular proliferation and differentiation during early mammalian development. Thus, the aim of this study was to identify exosomal-miRNAs in maternal blood at 21 days of gestation that could be used for diagnosis and prognosis during early clone pregnancies in cattle. Out of 40 bovine-specific miRNAs, 27 (67.5%) were with low abundance in the C-EPL (Clone - Early pregnancy loss) group compared with the C-LTP (Clone - Late pregnancy) and AI-LTP (Artificial Insemination - Late pregnancy) groups, which had similar miRNAs levels. Bioinformatics analysis of the predicted target genes demonstrated signaling pathways and functional annotation clusters associated with critical biological processes including cell proliferation, differentiation, apoptosis, angiogenesis and embryonic development. In conclusion, our results demonstrate decreased exosomal-miRNAs in maternal blood at 21 days of gestation in cloned cattle pregnancies that failed to reach term. Furthermore, the predicted target genes regulated by these 27 miRNAs are strongly associated with pregnancy establishment and in utero embryonic development.